Přestavba rodinného domu v proluce - Nevrlý, Jaroslav (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Projektová dokumentace řeší jednogenerační rodinný dům. Jedná se o řadovou zástavbu. Stavba má tři podlaží. Rodinný dům je nepodsklepený s plochou a pultovou střechou. Konstrukční systém tvoří svislé zděné stěny z keramických tvárnic a železobetonové sloupy.Stropy z keramických nosníků a vložek. Střecha je jednoplášťová. Stavba je založena na základových pasech a patkách.

Project documentation addresses the single-family house. It is a terraced houses.The building has three floors. House is a no basement with flat roof and shed roof. The structural system consists of a vertical brick wall of ceramic bricks and reinforced concrete columns. Ceilings, beams and ceramic inserts. The roof is asingle casing. The construction is based on strip foundations and footings.
Rebuilding of family house at vacant lot
Keywords: Rodinný dům; tři podlaží; nepodsklepený; základové pásy; základové patky; zděné stěny; monolitické železobetonové sloupy; keramický strop; plochá; střecha; pultová střecha.; Detached house; three floors; no basement; strip foundations; footings; brick; walls; concrete columns monolithic; ceramic ceiling; flat roof; shed roof